(untitled) (Jurnal Ilmu Manajemen dan Bisnis, 2023)
This research aims to find out the participation of the community in village development planning in Tolomato Village of Central Suwawa Subdistrict, and community participation in the implementation of Development in Tolomato Village of Central Suwawa Subdistrict. The method in this research uses qualitative research methods of research that intend to understand the phenomenon of what is experienced holistically, and by way of description in the form of words and language, in a special context to provide solutions or input to problems that are appropriate and related to the problem. The results of the research are: 1) community participation in development planning in Tolomato Village community and the government has both participated in village development planning although not all communities who participate in village development planning; and 2) community participation in the implementation of Tolomato Village has been good done by the community in forming village government to carry out village development in terms of participation in the form of energy and energy. Thoughts given by society.